Piloting puberty content books and a teacher training guide in Sierra Leone: a qualitative assessment - Martinez, Susi; Marfo, Sylvia Ohene; Ibrahim, Aisha Fofana; Carney, Allison; Vavrus, Frances; Kabba, Mohamed; Wyss, Natalie; Sommer, Marni (Frontiers in Education, 2024)
Ensuring young people receive adequate information and guidance about puberty is essential for healthy adolescent transitions. Although many countries are moving toward including comprehensive sexuality education in national curricula, content on puberty during early adolescence, including peer pressure and stigma related to physical and emotional changes, are rarely included. Limited evidence exists about the inclusion of puberty education in schools, and the role of teachers in delivering such content in low-and middle-income countries, including Sierra Leone. We conducted a qualitative assessment using multiple methodologies (in-depth interviews with teachers; focus group discussions with girls and boys; key informant interviews with teacher training lecturers and government) to explore the feasibility and acceptability of a puberty education package (a teacher training guide and boys' and girls' puberty books) for primary school teachers to introduce puberty content in Sierra Leone. Three key themes were identified, including the importance of teacher comfort in discussing puberty, the value of the teacher's guide for delivering puberty content, and system and resource constraints that impact the implementation of puberty education. Additional insights included how integrating puberty education into existing curriculum courses may be more effective than stand-alone puberty classes; education systems can enable in-service and pre-service teacher training, along with culturally appropriate puberty resources, to increase effective puberty education delivery in schools; and governments serve a key role in providing puberty education teacher training, ensuring sustainable funding to retain trained teachers, and offering guidance on national curriculum requirements on puberty education. There is a strong need to integrate puberty education into formal educational systems, with well trained teachers serving a valuable role in its delivery. Research is needed on how best to scale sustainable teacher training interventions to support the delivery of puberty education to adolescents in low-and middle-income contexts.